Exploring the possibility of using fluorine-involved non-conjugated electron-withdrawing groups for thermally activated delayed fluorescence emitters by TD-DFT calculation - Chen, Dongyang; Zysman-Colman, Eli (Beilstein Journal of Organic Chemistry, 2021)
The trifluoromethyl group has been previously explored as a non-conjugated electron-withdrawing group in donor–acceptor thermally activated delayed fluorescence (TADF) emitters. In the present study, we investigate computationally the potential of other fluorine-containing acceptors, trifluoromethoxy (OCF3), trifluoromethylthio (SCF3), and pentafluorosulfanyl (SF5), within two families of donor–acceptor TADF emitters. Time-dependent density functional theory calculations indicate that when only two ortho-disposed carbazole donors are used (Type I molecules), the lowest-lying triplet state possesses locally excited (LE) character while the lowest-lying singlet state possesses charge-transfer character. When five carbazole donors are present in the emitter design (Type II molecules), now both S1 and T1 states possess CT character. For molecules 2CzOCF3 and 5CzOCF3, the singlet energies are predicted to be 3.92 eV and 3.45 eV; however, the singlet-triplet energy gaps, ΔESTs, are predicted to be large at 0.46 eV and 0.37 eV, respectively. The compounds 2CzCF3, 2CzSCF3, and 2CzSF5, from Type I molecules, show significant promise as deep blue TADF emitters, possessing high calculated singlet energies in the gas phase (3.62 eV, 3.66 eV, and 3.51 eV, respectively) and small, ΔESTs, of 0.17 eV, 0.22 eV, and 0.07 eV, respectively. For compounds 5CzSCF3 and 5CzSF5, from Type II molecules, the singlet energies are stabilized to 3.24 eV and 3.00 eV, respectively, while ΔESTs are 0.27 eV and 0.12 eV, respectively, thus both show promise as blue or sky-blue TADF emitters. All these six molecules possess a dense number of intermediate excited states between S1 and T1, thus likely leading to a very efficient reverse intersystem crossing in these compounds.
Keywords: DFT calculation; pentafluorosulfanyl; spin-orbit coupling; TADF; trifluoromethoxy; trifluoromethylthio